Electrooxidation of Ethylene Glycol and Glycerol on Pd‐(Ni‐Zn)/C Anodes in Direct Alcohol Fuel Cells. Issue 3 (12th February 2013) - Marchionni, Andrea; Bevilacqua, Manuela; Bianchini, Claudio; Chen, Yan‐Xin; Filippi, Jonathan; Fornasiero, Paolo; Lavacchi, Alessandro; Miller, Hamish; Wang, Lianqin; Vizza, Francesco
Abstract The electrooxidation of ethylene glycol (EG) and glycerol (G) has been studied: in alkaline media, in passive as well as active direct ethylene glycol fuel cells (DEGFCs), and in direct glycerol fuel cells (DGFCs) containing Pd‐(Ni‐Zn)/C as an anode electrocatalyst, that is, Pd nanoparticles supported on a Ni–Zn phase. For comparison, an anode electrocatalyst containing Pd nanoparticles (Pd/C) has been also investigated. The oxidation of EG and G has primarily been investigated in half cells. The results obtained have highlighted the excellent electrocatalytic activity of Pd‐(Ni‐Zn)/C in terms of peak current density, which is as high as 3300 A g(Pd)−1 for EG and 2150 A g(Pd)−1 for G. Membrane‐electrode assemblies (MEA) have been fabricated using Pd‐(Ni‐Zn)/C anodes, proprietary Fe‐Co/C cathodes, and Tokuyama A‐201 anion‐exchange membranes. The MEA performance has been evaluated in either passive or active cells fed with aqueous solutions of 5 wt % EG and 5 wt % G. In view of the peak‐power densities obtained in the temperature range from 20 to 80 °C, at Pd loadings as low as 1 mg cm−2 at the anode, these results show that Pd‐(Ni‐Zn)/C can be classified amongst the best performing electrocatalysts ever reported for EG and G oxidation.